2023
DOI: 10.3389/fnins.2023.1087488
|View full text |Cite
|
Sign up to set email alerts
|

An fMRI study of visual geometric shapes processing

Abstract: Cross-modal correspondence has been consistently evidenced between shapes and other sensory attributes. Especially, the curvature of shapes may arouse the affective account, which may contribute to understanding the mechanism of cross-modal integration. Hence, the current study used the functional magnetic resonance imaging (fMRI) technique to examine brain activity’s specificity when people view circular and angular shapes. The circular shapes consisted of a circle and an ellipse, while the angular shapes con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 44 publications
0
1
0
Order By: Relevance
“…Abnormal functioning of both the precuneus and cuneus can indicate compromised integrity of the DMN, a phenomenon that is frequently observed in depression[ 26 ]. The cuneus, which is a crucial part of the visual recognition network and is situated in the occipital lobe of the brain, has the primary functions of processing visual data, facial perception, emotion, and working memory[ 27 ]. Gong et al [ 9 ] showed that, compared to control individuals, adolescents with MDD had lower ALFF values in the bilateral cuneus.…”
Section: Discussionmentioning
confidence: 99%
“…Abnormal functioning of both the precuneus and cuneus can indicate compromised integrity of the DMN, a phenomenon that is frequently observed in depression[ 26 ]. The cuneus, which is a crucial part of the visual recognition network and is situated in the occipital lobe of the brain, has the primary functions of processing visual data, facial perception, emotion, and working memory[ 27 ]. Gong et al [ 9 ] showed that, compared to control individuals, adolescents with MDD had lower ALFF values in the bilateral cuneus.…”
Section: Discussionmentioning
confidence: 99%